Podejście historyczno-religijne (analiza porównawcza) w egzegezie tekstów biblijnych - Szymik, Stefan (The Biblical Annals, 2015)
The author of the article deals with the comparative method in biblical exegesis. First he critically evaluates the results of the application of this method together with its principles and goals. In the second part of the article he analyzes the semantic range of the fundamental terms and opinions of different authors concerning the principles of religiohistorical comparison; then there follows his own conclusions concerning the application of the method. Finally, the author attempts to formulate his own description of the comparative method in biblical exegesis.